Ethnomathematics: Predicting the Average Height of the Bali Mula Ancestors using Linear Regression - Darmayasa, Jero Budi; W, Wahyudin; Mulyana, Tatang (Universitas PGRI Madiun, 2019)
This research is a study of Ethnomathematics. In this case, we view Ethnomathematics as an intersection between mathematics, mathematical modelling, and cultural anthropology. The purpose of this study is to determine the average height of Bali Mula ancestors communities in the area of Ancient Caldera Batur. We use exploration, observation, experimentation, documentation, and interviews method. In the initial stage of the study, we determine the relationship between the finger length index and the height body of Bali Mula male. The linear regression equation expresses the relationship, which is a length of the index finger as a predictor variable. Moreover, measure the pillars width of some houses Saka Roras and substituting it, we have the regression equation. Consequently, we estimate the average height of the Bali Mula ancestors in Kintamani area are 165 cm. Since it contains linier regression concepts, prediction the average height of Bali Mula ancestors from their traditional homes may be used as the context in mathematical (statistical) learning at school or university.